2009 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting 2009
DOI: 10.1109/isbmsb.2009.5133798
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of High Definition TV distribution over IP networks

Abstract: High Definition (HD) content delivery over IP networks has become a reality in the market of entertainment technologies. This paper presents a professional testbed deployed to emulate a real use case of delivering high definition TV material over an IPTV network. The quality of the delivered H.264/AVC encoded video was evaluated by common objective video quality assessment tools in emulated environment subject to impairments. Objective measurements were further validated by subjective tests. Based on the obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Our results show that users tolerate up to two visual impairments during movie playback, which corresponds with the recommended QoE requirements for SD. Issa et al [18] showed that in the case of HDTV, the recommended mean time between visible distortions can be relaxed to some extent. As a final result, we tested the significance between the MOS scores of SNR and temporal downscaled short sequences.…”
Section: Mosmentioning
confidence: 99%
“…Our results show that users tolerate up to two visual impairments during movie playback, which corresponds with the recommended QoE requirements for SD. Issa et al [18] showed that in the case of HDTV, the recommended mean time between visible distortions can be relaxed to some extent. As a final result, we tested the significance between the MOS scores of SNR and temporal downscaled short sequences.…”
Section: Mosmentioning
confidence: 99%
“…Subjective tests were also conducted in related works, but only one bitrate (12MBit/s) and interlaced material was considered [5], [6]. Also only one setting for H.264/AVC was used in these contributions and no alternative encoders were included.…”
Section: Introductionmentioning
confidence: 99%
“…Network losses are considered additionally, with a lower stress put on it. Another research published recently in [9] is dedicated exclusively to network losses. Correlation of three existing quality metrics was verified upon the subjective results, namely PSNR, SSIM [10] and VQM [7].…”
Section: Introductionmentioning
confidence: 99%